Baseline fat fraction is a strong predictor of disease progression in Becker muscular dystrophy. (5th February 2022) - Veeger, Thom T. J.; van de Velde, Nienke M.; Keene, Kevin R.; Niks, Erik H.; Hooijmans, Melissa T.; Webb, Andrew G.; de Groot, Jurriaan H.; Kan, Hermien E.
Abstract : In Becker muscular dystrophy (BMD), muscle weakness progresses relatively slowly, with a highly variable rate among patients. This complicates clinical trials, as clinically relevant changes are difficult to capture within the typical duration of a trial. Therefore, predictors for disease progression are needed. We assessed if temporal increase of fat fraction (FF) in BMD follows a sigmoidal trajectory and whether fat fraction at baseline (FFbase) could therefore predict FF increase after 2 years (ΔFF). Thereafter, for two different MR‐based parameters, we tested the additional predictive value to FFbase. We used 3‐T Dixon data from the upper and lower leg, and multiecho spin‐echo MRI and 7‐T 31 P MRS datasets from the lower leg, acquired in 24 BMD patients (age: 41.4 [SD 12.8] years). We assessed the pattern of increase in FF using mixed‐effects modelling. Subsequently, we tested if indicators of muscle damage like standard deviation in water T2 (stdT2 ) and the phosphodiester (PDE) over ATP ratio at baseline had additional value to FFbase for predicting ∆FF. The association between FFbase and ΔFF was described by the derivative of a sigmoid function and resulted in a peak ΔFF around 0.45 FFbase (fourth‐order polynomial term: t = 3.7, p < .001). StdT2 and PDE/ATP were not significantly associated with ∆FF if FFbase was included in the model. The relationship between FFbase and ∆FF suggests a sigmoidal trajectory of the increase in FF over time in BMD, similar to that described for Duchenne muscular dystrophy. Our results can be used to identify muscles (or patients) that are in the fast progressing stage of the disease, thereby facilitating the conduct of clinical trials. Abstract : We found a sigmoidal temporal progression of fat fraction (FF) in lower extremity muscles of Becker muscular dystrophy patients, evidenced by the bell‐shaped relationship between baseline FF (FFbase) and FF increase (∆FF). This can be used to identify muscles that are in the fast progressing stage of the disease, thereby facilitating the conduct of clinical trials. Neither baseline standard deviation T2 (stdT2 ) nor phosphodiester (PDE) over ATP ratio, markers for muscle cell/membrane damage, were associated with ∆FF.